Board effectiveness and carbon emission disclosure: evidence from ASEAN countries - Marwan Mansour; Almothanna Jamil Abu-Allan; Sajead Mowafaq Alshdaifat; Dheif Allah E’leimat; Mohammed W. A. Saleh (Discover Sustainability)
Abstract This study investigates how corporate board governance attributes influence carbon emission disclosure (CED) across ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) from 2015 to 2022. Using panel data regressions and a composite Board Effectiveness Score, the analysis evaluates both individual board characteristics—gender diversity, size, independence, meeting frequency, and environmental committees—and their collective impact on CED as measured by CDP scores. Grounded in agency, resource dependence, stakeholder, legitimacy, signaling, and voluntary disclosure theories, the findings reveal that gender diversity and the presence of an environmental committee significantly enhance CED, supporting the notion that board diversity and specialized structures improve sustainability oversight. In contrast, board size and meeting frequency show no consistent influence, challenging conventional assumptions within agency and stakeholder theories. Notably, board independence has a negative impact on disclosure, highlighting contextual governance challenges in the ASEAN region. The Board Effectiveness Score emerges as a stronger predictor of CED than individual attributes, confirming that integrated governance mechanisms better explain corporate transparency. Additional robustness tests—including quantile regression, logit analysis, and dynamic GMM—confirm the consistency of results. Control variables such as green innovation, firm size, age, and profitability also positively affect disclosure. As one of the first region-wide governance studies in Southeast Asia, this research provides important implications for policymakers, investors, and sustainability advocates, underscoring the need for enhanced governance frameworks and regulatory mandates to bridge ASEAN’s sustainability disclosure gap and align corporate practices with global climate goals.